The Effect of Remnant Preservation on Tibial Tunnel Enlargement in Anterior Cruciate Ligament Reconstruction with Polyethylene Terephthalate Artificial Ligament in a Large Animal Model - Cai, Jiangyu; Wan, Fang; Ai, Chengchong; Jin, Wenhe; Sheng, Dandan; Liu, Xingwang; Wang, Siheng; Zhi, Yunlong; Chen, Jun; Chen, Shiyi (The Journal of Knee Surgery, 2019)
An enlarged bone tunnel may affect the graft–bone integration and pose a problem for revision anterior cruciate ligament (ACL) surgery. The purpose of this study was to evaluate the effect of remnant preservation on tibial tunnel enlargement in ACL reconstruction with polyethylene terephthalate (PET) artificial ligament. Twenty-four skeletally mature male beagles underwent ACL reconstruction with PET artificial ligament for both knees. One knee was reconstructed with remnant preservation using sleeve technique (remnant group), while the contralateral was reconstructed without remnant preservation (control group). The animals were sacrificed at 1 day, 6 weeks, and 12 weeks after surgery for further evaluation including macroscopic observation, microcomputed tomography (micro-CT), histological assessment, and biomechanical testing. The remnant group had better synovial coverage than the control group at 6 and 12 weeks after surgery. The micro-CT analysis showed the tibial tunnel area (TTA) of the remnant group was significantly smaller and the bone volume/total volume fraction (BV/TV) value was higher than those of the control group at 6 and 12 weeks. Moreover, TTA and BV/TV at each time point were divided into three groups according to the different grade of synovial coverage. Significant association was observed between the synovial coverage degree and the TTA and BV/TV values. The histological assessment revealed that the interface width between the graft and host bone in the remnant group was smaller than that in the control group in the tibial tunnels at 6 and 12 weeks. Moreover, the remnant group had better failure load and stiffness than the control group at 12 weeks. The remnant preservation using sleeve technique could effectively promote the synovial coverage of the graft, decrease the risk of tibial tunnel enlargement by sealing the bone tunnel entrance, and enhance the biological environment for graft–bone healing after ACL reconstruction using PET artificial ligament. This technique provides a potential solution for bone tunnel enlargement following artificial ligament surgery for the acute ACL rupture in the clinical practice.
Keywords: remnant preservation; bone tunnel enlargement; anterior cruciate ligament; polyethylene terephthalate; artificial ligament